POTRET DAKWAH NABI IBRAHIM AS.: Kajian Nilai-Nilai Teologi dan Moralitas Perspektif Pragmatika Al-Qur’an - Moh. Fuad Miftah Romadhan; Faishal Khair (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract The incessant contestation of da'wah has given the community ample opportunities for expression. However, those who lack religious insight often disregard the fundamental principles and values that should form the basis of da'wah. This situation is concerning for Muslims as it could potentially become a parasite on the existence of the Islamic religion itself. Meanwhile, the Qur'an contains many verses containing ibrah (lessons) regarding the pattern of da'wah through the presentation of stories. Therefore, to refresh the da'wah pattern that is offensive, open, and humanistic, the author will examine the verses of the Qur'an that tell the story of the da'wah of the Prophet Ibrahim. There are two things that the author will discuss, namely: 1) What are the theological values of the Prophet Ibrahim's da'wah? 2) what are the moral values of the Prophet Ibrahim's da'wah? The following two formulations will be revealed based on the pragmatic perspective of the Qur'an by focusing on two theories: speech act theory to assess the speaking patterns of Prophet Ibrahim when doing da'wah and implicature theory to find the intended value based on the implications of the speech expressed by Prophet Ibrahim. The research concludes: First, The theological values in the da'wah of Prophet Ibrahim prioritize rationality and reject religious fanaticism propaganda and tyranny. The da’wah model of Prophet Ibrahim embodies these values. Second, The value of morality in the da'wah of Prophet Ibrahim is evident in his polite attitude in da'wah towards his parents and his courage to uphold the truth through non-verbal means (da'wah bil hal), as well as da'wah through parenting models to children which are carried out persuasively and offensively. Keywords: Da'wah, Theological Values, Moral Values, Pragmatics of the Qur'an